2020
DOI: 10.1140/epjc/s10052-020-08647-8
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement of purification near a critical point

Abstract: In the presence of finite chemical potential $$\mu $$ μ , we holographically compute the entanglement of purification in a $$2+1$$ 2 + 1 - and $$3+1$$ 3 + 1 -dimensional field theory and also in a $$3+1$$ 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The above proposals pass a variety of consistency checks which provide important pieces of evidence for finding holographic duals of EWCS. See [13][14][15][16][17][18][19][20] for various studies of general properties of EWCS and its holographic counterparts in static geometries. Further, the nonequilibrium evolution of EWCS for various quench protocols has been considered in [21][22][23][24][25][26].…”
Section: Jhep08(2021)038mentioning
confidence: 99%
“…The above proposals pass a variety of consistency checks which provide important pieces of evidence for finding holographic duals of EWCS. See [13][14][15][16][17][18][19][20] for various studies of general properties of EWCS and its holographic counterparts in static geometries. Further, the nonequilibrium evolution of EWCS for various quench protocols has been considered in [21][22][23][24][25][26].…”
Section: Jhep08(2021)038mentioning
confidence: 99%
“…Different aspects of this background have been investigated. Indeed, it was shown that various quantities such as R-charge conductivity [40], complexity [41], mutual information [42] and entanglement of purification [43,44] remain finite, while their slopes diverge at the critical point with the same critical exponent θ = 1 2 . The value of the dynamical critical exponent was also confirmed in [45] and [46] by studying the non-hydrodynamical quasi normal modes (QNMs) of the external fields and quantum quench in this background, respectively.…”
Section: Jhep05(2021)287mentioning
confidence: 99%
“…As mentioned before, the theory we study in this paper enjoys a critical point at µ = πT / √ 2. The behavior of different observables near this critical point has been studied in [40][41][42][43][44][45][46]. In all cases it was shown that the critical exponent is θ = 1 2 .…”
Section: Critical Exponentmentioning
confidence: 99%
“…To date, its understanding in the intersection of quantum information science and high-energy physics is based on Gaussian calculations [27][28][29], usage of CFT techniques with a limited range of applicability [30][31][32] and, finally, on a conjectured realization in holography [33,34]. It is worth pointing out that in the latter case, EoP is conjectured to be dual to the entanglement wedge cross section [35][36][37][38] for which a variety of results have been found ranging from connections with multipartite states to thermal states (see e.g., [39][40][41][42][43][44][45][46][47][48][49]) and is thus pivotal to the efforts of understanding bulk reconstruction in holography [50]. The aim of this letter is to to elucidate what perhaps is the simplest setting in which EoP behaves universally across CFTs and does not rely on Gaussianity nor on local conformal transformations.…”
Section: Fig 1 Entanglement Of Purification On An Infinite Latticementioning
confidence: 99%